(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Coffee consumption in relation to female hormone-related cancers has been investigated but metaanalyses regarding breast and ovarian cancer include studies published up to 2012 with inconsistent results for ovarian cancer. Methods: We conducted two updated meta-analyses of studies published up to June 2016 to quantify the association of coffee intake with breast and ovarian cancer risk with random effects models. We used the dataset developed by the International Agency for Research on Cancer Working Group for Monograph 116 meeting (May 2016). We additionally performed a PubMed search in June 2016. Results: Summary relative risks (RRs) (95% confidence intervals (CI)) for the study-specific highest vs. lowest coffee consumption were for breast and ovarian cancer respectively: 0.97 (0.93–1.00, Ι2 5.5%, 40 studies, 76,728 cases) and 1.03 (0.93–1.14, Ι 2 31.9%, 31 studies, 13,111 cases). For decaffeinated coffee the corresponding RRs were: 1.00 (0.93-1.08, I2 32.2%, 13 studies) and 0.83 (0.71-0.96, I2 about 0%, 9 studies). The association of coffee with ovarian cancer risk was higher among publications before (RR=1.37, 1.12–1.69) compared to after 2000 (RR=0.96, 0.86-1.06). Conclusion: Our meta-analyses provide strong, quantitative evidence that coffee consumption is not related to breast cancer risk and appears to be unrelated to ovarian cancer risk.